Dietary Resistant Potato Starch Alters Intestinal Microbial Communities and Their Metabolites, and Markers of Immune Regulation and Barrier Function in Swine - Trachsel, Julian; Briggs, Cassidy; Gabler, Nicholas K.; Allen, Heather K.; Loving, Crystal L. (Frontiers in Immunology, 2019)
Interactions between diet, the microbiota, and the host set the ecological conditions in the gut and have broad implications for health. Prebiotics are dietary compounds that may shift conditions towards health by promoting the growth of beneficial microbes that produce metabolites capable of modulating host cells. This study’s objective was to assess how a dietary prebiotic could impact host tissues via modulation of the intestinal microbiota. Pigs fed a diet amended with 5% resistant potato starch (RPS) exhibited alterations associated with gut health relative to swine fed an unamended control diet (CON). RPS intake increased abundances of anaerobic Clostridia in feces and several tissues, as well as intestinal concentrations of butyrate. Functional gene amplicons suggested bacteria similar to Anaerostipes hadrus were stimulated by RPS intake. The CON treatment exhibited increased abundances of several genera of Proteobacteria (which utilize respiratory metabolisms) in several intestinal locations. RPS intake increased the abundance of regulatory T cells in the cecum, but not periphery, and cecal immune status alterations were indicative of enhanced mucosal defenses. A network analysis of host and microbial changes in the cecum revealed that regulatory T cells positively correlated with butyrate concentration, luminal IgA concentration, expression of IL-6 and DEF1B, and several mucosa-associated bacterial taxa. Thus, the administration of RPS modulated the microbiota and host immune status, altering markers of cecal barrier function and immunological tolerance, and suggesting a reduced niche for bacterial respiration.